O encontro da luz com as trevas : uma análise do pós-colonialismo através de Heart of Darkness - Santos, Lidiana de Moraes dos (2012)
The goal with the present study is to reread the work Heart of Darkness, written by Joseph Conrad, through a post-colonial perspective. First a review of the post-colonial theory was made. With the study of the writings of authors such as Edward Said, Homi K. Bhabha and Gayatri Chakravarty Spivak will be possible to comprehend the post-colonial thought. Also, some literary texts were revisited in a way that their colonialist points of view help to built a counterpoint to the post-colonial precepts. In a second moment, Heart of Darkness was analyzed in a special way, through the recovery of meaningful parts of the text that can illustrate the mistakes and understandings of the criticisms made to Conrad s literary text by names that emerged in the post-colonial period, such as the Nigerian author, Chinua Achebe. With this rereading we aim to perceive the true message that Joseph Conrad wanted to send by telling the story of Kurtz and Marlow as explorers in Africa.